Exploring the “Chilly Climate” at an Indian Liberal Arts College: Is There a Thaw? - Jui Shankar; Aashna Banerjee; Mellisa Holtzman (Women, Education, and Social Welfare, 2026)
The existence of gendered environments within college classrooms is often referred to as the “chilly climate.” Historically, classrooms and campus climates in many universities have reinforced gender bias against female students. However, higher education institutions that embrace critical pedagogies and liberal arts learning may be able to improve campus climates because these educational practices often emphasize dismantling existing inequities and oppressive structures. Thus, it is meaningful to ask if the transformative learning experiences fostered by critical pedagogies and the liberal arts might help thaw the chilly climate. To explore this possibility, we use student experiences from an Indian higher education institution as a case study. More specifically, we interviewed students who were attending a college in western India that has a long-standing commitment to critical pedagogies and the liberal arts. Findings illustrate that students continue to experience gender bias in their classrooms, even though campus policies and practices explicitly promote social equality and transformative learning spaces. This suggests that embedding critical pedagogies into university vision statements and classroom experiences may not be sufficient to thaw the chilly climate; institutional-level actions that explicitly and concretely target the chilly climate will also be necessary. Implications for higher education policies are discussed.